The impact of capital from experience on the value of an employee’s fair remuneration - Oliwkiewicz, Barbara (Wpływ kapitału z doświadczenia na wartość godziwego wynagrodzenia pracownika, 2019)
Human capital is a category that has been the subject of economists’ considerations for years. Numerous concepts, research approaches and various ways of classifying capital have appeared. Since the 1990s, in accordance with the fundamental principle of dualism, according to which capital is an abstract category, an alternative scientific research program has been conducted in the field of measuring human capital and fair wages. This program was initiated by M. Dobija and has been followed by a team of researchers from the Cracow University of Economics. The program in question is based on a proper understanding of the capital category. It has been consistently developing, and the scientific research covers a wide range of theories related to human capital and fair remuneration. The purpose of this study is to present the impact of capital from experience on the level of the fair remuneration of employees. The human capital model, in the presented considerations enables the measurement of employee qualifications in monetary units and a fair pay model. A case study on the impact from experience capital on the level of fair remuneration of employees was also presented
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 10, s. 207-220